The Role of Energy Resources in Economic Warfare - Marek SZTURO (Communications of International Proceedings, 2025)
This article examines the role of energy resources as a strategic instrument in economic warfare. The analysis focuses on how states and other actors employ oil, gas, and other energy commodities to exert political and economic pressure, shape international relations, and achieve geopolitical objectives. Particular attention is given to the consequences of such practices for global energy security, market stability, and the economic resilience of both resource-dependent and resource-supplying countries. The study aims to assess the long-term impacts of using energy resources in economic warfare and to highlight the challenges this poses for international cooperation and sustainable development.
Keywords: energy resources; energy security; economic conflict.